HUBUNGAN ANTARA CENDAWAN MIKORIZA ARBUSKULA INDIGENEOUS DAN SIFAT KIMIA TANAH DI LAHAN KRITIS TANJUNG ALAI, SUMATERA BARAT - Muzakkir Muzakkir (Jurnal Solum, 2011)
Critical land is land that has lost its function as an agro-ecosystem. The main problems faced in using critical land for agriculture are: 1) acidic soil reaction, 2) high amount of Al ions that can bind phosphorus, and 3) low organic matter content. Some treatment had been tried to improve soil chemical properties, but the result obtained is not optimal. Therefore, it is necessary to do biological improvement by utilizing indigeneous Arbuscular Mycorrhizal Fungi (AMF).  Research on the relationship between Indigeneous Arbuscular Mycorrhizal Fungi and some chemical properties of degraded land have been carried out at the Laboratory of Soil Science and Microbiology Department, Faculty of Agriculture, Andalas University ( UNAND). This study was  aimed to determine the relationship between the number and types of AMF with some chemical properties of critical land in Tanjung Alai Solok, West Sumatra, as well as to study the relationship between the number and types of AMF with some soil chemical properties using Pearson correlation analysis.  The results showed that: the number and types of AMF is closely related to pH, P, and organic C, with a pattern of positive relationships (unidirectional), while Al-dd soil showed negative correlation with the number and types of AMF.Keywords: critical land, AMF, soil chemical properties